Some natural heritages of outstanding values for tourism development in Central Highland - Phuong, Ta Hoa; Hai, Truong Quang; Bao, Dang Van (Vietnam Journal of Earth Sciences, 2015)
Tay Nguyen or the Central Highland with the remains of Archean relics is known as the region of the oldest natural formation across Vietnam’s territory. Had been taking place in the Central Highland the combined tectonic activities with typical exogenous process of the Cenozoic. Tay Nguyen contains many valuable natural resources, especially natural heritages that facilitate the development of ecotourism and scientific tourism. Scope of the TN3/T18 national project as part of the Central Highland Program 3 mainly covers research on the outstanding values, including 1) Some areas of extraordinary beauty and aesthetic value such as Dray Nur and Dray Sap waterfalls on the Serepok River in Dak Lak and Dak Nong provinces. 2) Fossil of the yews discovered in the Chu A Thai mountain, Phu Thien district, Gia Lai province; 3) Typical “living fossil plants” of the Central Highland that still exist such as yews (Glyptostrobus pensilis) and two flat-leaf pine-trees (Ducampopinus krempfii) in Gia Lai and Lam Dong; 4) Stone of the Kan Nack series (NA-PP) that is one of the oldest nationwide in basins of the Ba river, Gia Lai province; 5) Spectacular volcano landscape in Gia Lai and Kon Tum; 6) The unique cave system in the Krong No area, formed in basalt layer, is of fundamental difference from Vietnam’s popular limestone caves.ReferencesBonface B. G., Cooper C., 2012: Worldwide Destinations: The Geography of Travel and Tourism, Publishing House Routledge, p.610. Võ Văn Chi. 2004: Từ điển Thực vật thông dụng (Tập 2). Nxb. Khoa học và Kỹ thuật, Hà Nội, 2698tr. La Thế Phúc, Trương Quang Quý, Đỗ Chí Kiên, 2010: Di sản địa chất liên quan đến đá basalt ở Tây Nguyên và các giải pháp bảo tồn phát triển bền vững. Số đặc biệt kỷ niệm 65 năm ngày truyền thống ngành Địa chất Việt Nam. TC Địa chất. Hà Nội, 320, 514-521. La Thế Phúc, Lương Thị Tuất, Trương Quang Quý, 2012: Hang động trong đá basalt ở Cư Jut, Đắk Nông, Việt Nam. Hội nghị Công viên Địa chất Toàn cầu năm 2012 tại Unzen, Nhật Bản, tháng 5/2012. Nguyễn Thành Mến, 2013: Một số đặc điểm quần thể và phân bố loài Thông hai lá dẹt (Pinus krempfii H. Lec) ở Lâm Đồng. Tạp chí Khoa học Lâm nghiệp số 1, năm 2012, tr.2095-2104. Trương Quang Quý, La Thế Phúc, 2010: Trinh Nữ waterfall geologicall heritage, Đắk Nông province. Journal of Geology; series B.35-36/2010; 131-139. Hà Nội: Department of Geology and Minerals of Vietnam. H. Tachihara, TS. T. Honda, 2014: Báo cáo kết quả nghiên cứu sơ bộ các hang động núi lửa ở Đắk Nông, Việt Nam. Hội nghị Thông cáo báo chí “Công bố kết quả khảo sát hang động núi lửa tại khu vực Krông Nô, tỉnh Đắk Nông, Tây Nguyên Việt Nam” ngày 26/12/2014 tại Tổng cục Địa chất và Khoáng sản Việt Nam, số 6 Phạm Ngũ Lão, Hà Nội. Tong Dzuy Thanh, Vu Khuc (Editors), et al., 2006: Stratigraphical units of Vietnam. Vietnam National University Publishing House. Hanoi. 528 pgs. (2012 in lần thứ 2). Trần Văn Trị, Vũ Khúc (Editors) và nnk. 2012: Geology and Earth Resources of Vietnam. Publishing House for Science and Technology, Hanoi. 636 pgs. Wolfgang Eder, 2004: Geoparks - geological attractions: A tool for public education, recreation and sustainable economic development. UNESCO, Division of Earth Sciences, 1, rue Miollis, F-75732 Paris Cedex 15, France.